Practice for Completing Corporate Tax Return in Tax Payers at Cooperatives Universitas Muhammadiyah Purwokerto - Ani Kusbandiyah; Iwan Fakhruddin; Rezky Pramurindra (Journal of Society, Community and Business Development, 2024)
The aim of this Community Service is to increase insight and competence in the field of taxation, especially in understanding the calculation and filling out of Corporate Tax Returns. The object of this community service activity is the prosperous employee cooperative of Muhammadiyah University, Purwokerto. There are forms of training in the form of filling in e-SPT for Corporate Taxpayers to increase tax competency for employees in the finance department who also serve in the tax department, in filling out SPT online using the e-Form application. The method or method used in this Community Service Activity is firstly using a survey method, where the team conducts a survey directly to the location for initial data collection. Apart from conducting surveys, the team also carried out observations and interviews. These observations and interviews are carried out at an early stage in order to collect data and look for problems before deciding what kind of service activities are appropriate for the target audience. Interviews were conducted with the chairman of the cooperative and employees of the finance and taxation department.